Myotonic Dystrophy presenting as chronic diarrhoea and anal incontinence:A Case Report - Subrata Chakrabarti; Koushik Pan (International Journal of Medical Research and Review, 2014)
Myotonic dystrophy (MD) or Steinert's disease is a rare cause of chronic diarrhoea and anal incontinence. We present the case of a 37 year old man who presented with chronic diarrhoea and faecal incontinence as the initial symptoms to our outpatient clinic and was later diagnosed with MD. In the presence of chronic diarrhoea and faecal incontinence with muscle weakness, neuromuscular disorders such as myotonic dystrophy should be considered in the differential diagnosis.